Petrographic Characterization of Geological Settings in the Locality of Mabuku in the Territory of Beni, DRC - Deogratias Anguandia Odhipio; Maombi Kalimuli Kakule; Robert Nandefo Wazi (Indonesian Journal of Earth Sciences, 2022)
The geology of the DRC has already been studied on regional plans, on the scale of a province or territory. But these studies are too synthetic and they do not consider the variations of petrographic facies that can occur at the scale of a locality or a village. Thus, to overcome this possibility, the present study aims to make a petrographic characterization of the rocks of the locality of Mabuku in the territory of Beni. To achieve this, we proceeded by a microscopic analysis of 10 field samples (selected on the basis of the variability of the petrographic characteristics of the rocks). Analyzes of these samples at the petrographic laboratory of the University of Nairobi in Kenya at the LPA and LPNA revealed that the lithology of the Mabuku locality consists of orthogneiss, schists, dolerite and diorite intrusions, quartzites , laterite and sandstones. However, there are four dominant formations. These are the orthogneiss found to the north; schist, dominant in the eastern part; doleritic intrusions in the northwest part; and the sandstones which are distributed along a SW-NE diagonal. Nevertheless, important gaps remain to be completed from the geochemical and metallogenic point of view in the locality of Mabuku.